Doenças de chinchilas (Chinchilla lanigera) - Lucena, Ricardo Barbosa de (2012)
Diseases of chinchilla were studied through the review of necropsy reports of 202 postmortem examination carried out in this species from January 1997 to December 2011. One hundred and eighty nine of these necropsies (93.5%) had a conclusive diagnosis and in 13 (6.5%) a conclusive diagnosis was not reached due either absence of lesions or advanced autolysis. One hundred and sixty two (80%) of the necropsied chinchilla were females and 37 (18%) were males and the sex was not recorded in four cases (2%). Ages of necropsied chinchillas varied from one day to 12-years-old. The encountered diseases were grouped in the following categories: inflammatory diseases, diseases caused by intoxications, diseases caused by physical agents, metabolic diseases, parasitism, degenerative diseases, circulatory disturbances, developmental disorders and other disorders . Inflammatory diseases were the most prevalent (52 cases [25.7%]) and included gastritis (10 cases), necrotizing enteritis (6 cases), septicemia (5 cases), listeriosis (5 cases), bacterial bronchopneumonia (4 cases), pyometra (4 cases), diarrhea associated with Proteus sp. (3 cases), subcutaneous and lymph node abscesses (2 cases), endometritis (2 cases), otitis (2 cases), pyelonephritis (2 cases), abscesses in hepatic the round ligament (1 cases), fibrinous pneumonia (1 case), interstitial pneumonia (1 case), hepatitis and cholecystitis associated with Salmonella sp. (1 case), pulmonary histiocytosis (1 case), lymphohistiocytic miositis (1 case), and dermatophytosis by Trichopyton mentagrophytes (1 case). The second most prevalent group of diseases was that caused by intoxications (22,3% of the cases) including 45 cases of intoxication by salinomycin. Diseases caused by physical agents (21 cases [10.4%]) included trauma cases caused by other animals (8 cases), self mutilation secondary to intramuscular injection (8 7 cases), rectal prolapsed (3 cases) and dystocia (2 cases). Metabolic diseases were represented by 16 cases (7.9%) of hepatic lipidosis. Parasitic diseases were represented by 8 cases (4%) flea (4 cases) lice (4 cases) infestations and one case o giardiasis. Five cases (2.5%). Degenerative diseases (5 cases or 2,5%) included two cases of chronic renal failure, one case of scattered hepatocellular necrosis and one case of muscle necrosis of unknown origin. Circulatory disturbances included two cases (0.99%) of congestive heart failure. Neoplasms were represented by two cases (0.99%) of gastric adenocarcinoma. Developmental disorders included one (0,5%) case of atresia ani associated with polycystic kidneys and absence of reproductive tract and large intestine. Thirty eight cases (18.8%) did not fit in any of the above categories and were placed as other disorders . In this category dental disease was the most commonly (8 cases or 9%) diagnosed disorder, followed by 14 cases of hyperthermia, tow cases of anemia, two cases of fat metaplasia of adrenal cortex and two cases of mucometra.